Chicken faecal microbiota and disturbances induced by single or repeated therapy with tetracycline and streptomycin - Videnska, Petra; Faldynova, Marcela; Juricova, Helena; Babak, Vladimir; Sisak, Frantisek; Havlickova, Hana; Rychlik, Ivan (BMC veterinary research, 2013)
BACKGROUND: In this study, we characterised the microbiota present in the faeces of 15- and 46-week-old egg laying hens before and after tetracycline or streptomycin therapy. In the first experiment, the layers were subjected to 7 days of therapy. In the second experiment, the hens were subjected to two days of therapy, which was repeated for an additional two days after 12 days of antibiotic withdrawal. This enabled us to characterise dynamics of the changes after antibiotic administration and withdrawal, and to identify genera repeatedly resistant to tetracycline and streptomycin. RESULTS: Real-time PCRs specific for Enterobacteriales, Lactobacillales, Clostridiales and Bifidobacteriales showed that changes in the microbiota in response to antibiotic therapy and antibiotic withdrawal were quite rapid and could be observed within 24 hours after the change in therapy status. Pyrosequencing of PCR amplified V3/V4 variable regions of 16S rRNA genes showed that representatives of the orders Clostridiales, Lactobacillales, Bacteroidales, Bifidobacteriales, Enterobacteriales, Erysipelotrichales, Coriobacteriales, Desulfovibrionales, Burkholderiales, Campylobacterales and Actinomycetales were detected in the faeces of hens prior to the antibiotic therapy. Tetracycline and streptomycin therapies decreased the prevalence of Bifidobacteriales, Bacteroidales, Clostridiales, Desulfovibrionales, Burkholderiales and Campylobacterales in faecal samples in both experiments. On the other hand, Enterobacteriales and Lactobacillales always increased in prevalence in response to both therapies. Within the latter two orders, Escherichia and Enterococcus were the genera prevalence of which increased after all the antibiotic treatments. CONCLUSIONS: The changes in microbiota composition induced by the antibiotic therapy were rapid and quite dramatic and only representatives of the genera Enterococcus and Escherichia increased in response to the therapy with both antibiotics in both experiments.
Keywords: metagenom; Real-Time Polymerase Chain Reaction; kur domácí; Chickens; antibakteriální látky; Female; streptomycin; tetracyklin; Feces; Bifidobacterium; Anti-Bacterial Agents; Tetracycline; Metagenome; feces; zvířata; Clostridium; ženské pohlaví; Lactobacillales; Animals; kvantitativní polymerázová řetězová reakce; Streptomycin; Enterobacteriaceae